Evolution of Our Understanding of Myeloid Regulatory Cells: From MDSCs to Mregs - Manjili, Masoud H.; Wang, Xiang-Yang; Abrams, Scott (Frontiers in Immunology, 2014)
The term Myeloid-Derived Suppressor Cells (MDSCs) was first suggested in 2007 in order to reflect on the origin and function of myeloid cells during immunosuppression in cancer and other pathologic conditions. Emerging evidence suggest that MDSCs suppress CTL and Th1 responses in malignant diseases while they regulate effective immune responses in parasitic and helminth infections as well as Th17 inflammatory response during autoimmune diseases. Based on these data the term myeloid regulatory cells (Mregs) more accurately reflects their function and interactions with different cells of the immune system during diseased conditions. Here, we provide evidence on the multifaceted function of Mregs during diseased states.